Rancang Bangun Sistem Informasi Pendataan Pasien Rawat Inap Berbasis Web - Erna Astriyani; Jihan Fahira; Dionysius Fajar Wicaksono (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
The computer is a tool that helps the information. In this case every individual, company, and institution that uses technology trends must develop the system that they have used, so that they are no longer out of date, because technology is always updated all the time. The service data processing system at Sitanala Hospital is currently still manual, so patients must wait long enough for treatment. There is no computerized treatment procedure in processing patient data, so data is scattered and easily lost. This shows the role of the system in the company is very important. Creating a computerized system for inpatient data collection systems, to get accurate, fast and precise information. The proposed system will display a menu of input data ranging from patients entering the inpatient room, the results of patient diagnoses, actions taken when translating, patient rooms until the date of the patient's discharge as well as a method of reporting patient data monthly to annual for the leadership discovery. The method used is descriptive data analysis method. The technique of collecting data, by making observations to the company, conducting interviews, and conducting library studies with books, literature, materials obtained during lectures relevant to the experience gained. Meanwhile, to analyze this research, it uses Unified Modeling Language (UML) to discuss the procedures and processes that are currently running.